Electromagnetic scattering by particles and particle groups : an introduction - Mishchenko, Michael I. (New York: CUP, 2014)
This self-contained and accessible book provides a thorough introduction to the basic physical and mathematical principles required in studying the scattering and absorption of light and other electromagnetic radiation by particles and particle groups. For the first time the theories of electromagnetic scattering, radiative transfer, and weak localization are combined into a unified, consistent branch of physical optics directly based on the Maxwell equations. A particular focus is given to key aspects such as time and ensemble averaging at different scales, ergodicity, and the physical nature of measurements afforded by actual photopolarimeters. Featuring over 120 end-of-chapter exercises, with hints and solutions provided, this clear, one-stop resource is ideal for self-study or classroom use, and will be invaluable to both graduate students and researchers in remote sensing, physical and biomedical optics, optical communications, optical particle characterization, atmospheric physics and astrophysics.
Appendix A-H 372-405p.; References 406-426p.; Index 427-435p.
Keywords: Stokes parameters; Weak localization; Foldy equations